Femtosecond mode-locked fiber lasers incorporating graphene-based saturable absorbers - Lau, Kuen Yao (2017)
The advancement of mode-locked fiber laser (MLFL) in femtosecond range has wide applications especially in biomedical sciences. For instance, femtosecond lasers are employed for cancer treatment at cellular level. MLFL is achieved by mode-locking regime with an appropriate mode-locker. Over the past few years, researchers have shown substantial interest in fabricating efficient saturable absorbers (SAs) as passive mode-locker due to its minimal weight, mechanically stable and highly nonlinear properties. Two-dimensional materials are popular for SA fabrication due to broadband and almost wavelength independent absorption. However, fabrication techniques to incorporate two-dimensional material in SAs involve tedious procedures especially wet chemicals. This research work focuses on the generation of femtosecond pulses utilizing two different types of sandwichstructured SA; graphene-polymethyl-methacrylate (PMMA) thin-film and graphene nanoplatelet (GNP) powder. The graphene/PMMA-SA is made through simple transfer procedure of the thin-film on a fiber ferrule. On the other hand, the GNP-SA is realized by mechanical exfoliation technique of GNP powder on a fiber ferrule. The optical characterization shows that graphene/PMMA-SA possesses larger modulation depth and lower insertion loss as compared to GNP-SA, thus leading to stronger saturable absorption for pulse shaping mechanism. The main aspect of the study is to validate the fabrication techniques through enhanced laser architectures in erbium-doped fiber laser (EDFL); single- and dual-lasing output. The cavity optimization is carried out for both lasing operation in order to achieve stable mode-locking operation in femtosecond range. For the optimized setup, the EDFL with graphene/PMMA saturable absorber is able to generate around 700 fs at approximately 1556 nm wavelength range. For dual-lasing MLFL generation, its main challenge is to have a balance net cavity gain at different wavelengths. For erbium materials, the interested lasing wavelengths are about 1530 nm and 1560 nm within its emission range. In order to minimize the complexity of configuration,most of the optical components are shared between these two lasing wavelengths. This research work proposes laser architectures that utilize common gain medium and SA. Two red/blue wavelength division multiplexers are employed to provide a mechanism to split/combine these two wavelength ranges. Based on the proposed laser architectures, lasing directions are also investigated; unidirectional and bidirectional. The optimized pulse width of 730 fs and 870 fs are obtained at 1530 nm and 1560 nm, respectively. These findings are achieved with the bidirectional MLFL architecture incorporating graphene/PMMA-SA. The achievement of this research work solves the limitation of optical pulses measured in picosecond range from previous works, while new architectures of dual-lasing mode-locked EDFLs are successfully designed and executed.